Fibroids - Abduljabbar, Hassan (IntechOpen, 2021)
Uterine fibroids are benign tumors of the smooth muscle of the uterus. They are the most common pathologic abnormalities of the female genital tract, occurring in 20%-50% of women older than 30 years. Some fibroids present with symptoms, whereas others are asymptomatic. The etiology of uterine fibroids is unclear. As such, this book presents comprehensive information on clinical presentation, diagnosis, and management of myoma. Chapters discuss symptoms such as bleeding, pain, and sexual dysfunction, as well as imaging modalities for diagnosis and options for treatment, including medications and surgery.